1977
DOI: 10.1677/joe.0.0740243
|View full text |Cite
|
Sign up to set email alerts
|

Release of Immunoreactive and Radioactively Prelabelled Endogenous (Pro-)Insulin From Isolated Islets of Rat Pancreas in the Presence of Exogenous Insulin

Abstract: To study the influence of insulin on its own secretion, collagenase-isolated islets of rat pancreas were prelabelled with [3H]leucine for 2 h. After washing the islets, (pro-)insulin release was stimulated by glucose in the presence or absence of exogenous insulin (up to 2-5 mu./ml). Hormone release was unchanged by the presence of exogenous insulin as judged by determination of both immunoreactive insulin and radioactivity incorporated into the proinsulin and insulin fractions of the medium. No direct feedbac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
23
0

Year Published

1980
1980
2002
2002

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 11 publications
3
23
0
Order By: Relevance
“…1 Because 5HT exposure exerts inhibitory effects on insulin release (8 -10), the precise physiologic significance of findings made with 5HT-preloaded ␤-cells is unclear. Moreover, previous studies exploring the potential role of insulin on stimulated secretion showed no effect (11) or supported the concept that insulin exerts a negative, not positive, feedback on its own secretion (12)(13)(14)(15).…”
mentioning
confidence: 54%
See 1 more Smart Citation
“…1 Because 5HT exposure exerts inhibitory effects on insulin release (8 -10), the precise physiologic significance of findings made with 5HT-preloaded ␤-cells is unclear. Moreover, previous studies exploring the potential role of insulin on stimulated secretion showed no effect (11) or supported the concept that insulin exerts a negative, not positive, feedback on its own secretion (12)(13)(14)(15).…”
mentioning
confidence: 54%
“…Because there is constitutive secretion of insulin, a tonic level of insulin signaling in these cells may influence acute stimulatory responses and thus obscure any effect of exogenously added insulin. These three issues, in addition to the use of different species and disparate methodological approaches, may account in part for the discrepancies regarding the impact of insulin on its own secretion (11,12,14,20,21). To circumvent the first problem, and to establish the effect of exogenously added insulin on its own secretion, we have measured connecting (C)-peptide secretion rates in response to a variety of agonists from isolated perifused rat islets.…”
mentioning
confidence: 99%
“…However, the evidence for a direct intraislet effect of insulin upon the B cell has been controversial owing to problems of experimental design, such as possible diffusion artifacts in isolated islet preparations, species differences between endogenous and exogenous insulin (6) and the necessity of measuring differences in endogenous insulin secretion during exogenous insulin infusion by indirect mathematical methods (2,3). Therefore, depending upon the system examined and the experimental design, exogenous insulin has either been suggested to have no effect upon endogenous insulin release (1,(7)(8)(9)(10) or to be inhibitory (2, 4-6, 1 1,12). Reports concerning in vitro self-inhibition by insulin have thus been inconclusive (1,2,6,8,9), although a recent report has suggested that exogenous insulin had no effect upon C-peptide secretion (10) from isolated rat islets.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, depending upon the system examined and the experimental design, exogenous insulin has either been suggested to have no effect upon endogenous insulin release (1,(7)(8)(9)(10) or to be inhibitory (2, 4-6, 1 1,12). Reports concerning in vitro self-inhibition by insulin have thus been inconclusive (1,2,6,8,9), although a recent report has suggested that exogenous insulin had no effect upon C-peptide secretion (10) from isolated rat islets. Reports from in vivo studies have not alleviated the controversy as to whether the inhibition of endogenous insulin secretion by exogenous insulin is from a direct or an indirect effect upon the B cell, even though measurements of C-peptide in vivo have demonstrated clearly that during glucose clamping exogenous insulin inhibits endogenous insulin release (4,5,7,11,12).…”
Section: Introductionmentioning
confidence: 99%
“…These high levels of insulin had three effects. First, they reduced endogenous insulin secretion (Dunbar et a/., 1976 ;Schatz and Pfeiffer, 1977) and therefore the rate of the disappearance of insulin from the circulation was overestimated. Secondly, the high levels reduced hepatic insulin extraction (Tranberg and Dencker, 1978 ; Harding, Bloom and Field, 1975 ;Mondon et al, 1975 ;Sonksen et al, 1973 ;Tiran, Avruch and Albisser, 1979 ;Honey and Price, 1979 ;Misbin, Mérimée and Lowenstein, 1976) and thirdly, they resulted in a decrease in blood glucose that is known to increase the metabolic clearance rate of insulin and the secretion of hyperglycaemic hormones (Brockman and Bergman, 1975 During each sampling day (except at 3 p.m.), the mean immunoreactive plasma insulin level was significantly lower (0.005 < P < 0.010) in the experimental than in thj control group ( fig.…”
Section: Introductionmentioning
confidence: 99%